A cationic polymer enhanced PAC for the removal of dissolved aquatic organic carbon and organic nitrogen from surface waters. (21st May 2018) - Wang, Chuang; Zhu, Guocheng; Ren, Bozhi; Zhang, Peng; Hursthouse, Andrew
Abstract: Dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) are important components of the aquatic environment and may produce harmful disinfection by‐products through chlorination associated with water treatment processes. Therefore, it is necessary to remove them from the water. Coagulation is a cost‐effective water treatment technique as the key unit in the pretreatment of drinking water but deals with DON poorly. We present a study to investigate the enhancement of poly aluminum chloride (PAC) using a cationic polymer for the removal of both DON and DOC. The cationic dimethyl diallyl ammonium chloride (PDMDAAC) polymer was hybridized with PAC to remove DON and DOC. The results showed that the PDMDAAC increased the charge neutralization capacity of PAC and floc aggregation, thereby increasing the settling efficiency of the flocs. The PDMDAAC increased the amount of colloidal species in PAC, which was beneficial to the formation of adsorption‐bridging. With the increase of pH, a greater proportion of colloidal adsorption sites were used in the removal of DON. The DOC, DON, and turbidity removal were dependent on multiple interactions through charge neutralization, adsorption‐bridging, and floc sweeping. However, DOC and DON removal were primarily determined by adsorption‐bridging and floc sweeping, while turbidity removal was mainly dependent on charge neutralization.